Effect of Canalplasty on Outcome of Results in Type I Tympanoplasty - Ajay Mallick; Vijay Bhalla; Ravi Roy (Bengal Journal of Otolaryngology and Head Neck Surgery, 2016)
Background: The aim of  the surgical procedure of tympanoplasty is to strive to achieve an intact neo tympanum with normal hearing acuity. Widening of the external auditory canal, called canalplasty,  helps in better visualization and hence better placement of the tympanic membrane graft. Aim of this study was to compare effect of canalplasty on the outcome of results of type I tympanoplasty.